Escolarização de crianças e adolescentes hospitalizados: do direito à realidade - Xavier, Thaís Grilo Moreira (2012)
The right of children and teenage to continue enjoying the school process during the hospitalization is guaranteed through resolution No. 02 of 2001 of the National Council of Education/Chamber of basic education. Despite so many laws and documents violations of those rights is a daily fact in Brazil. Our goals were to identify the design of managers of education and health professionals about the education of children and teenage during hospitalization; and seize the family conception of school-age children and teenage regarding the expulsion of the schooling process, during hospitalization. We use in our study the qualitative approach of exploratory type descriptive. The empirical material was produced through semi structured interview and focus group conducted in University Hospital Lauro Wanderley (HULW) and at the Children s Hospital Arlinda Marques (HIAM) in the period April to August 2011. The subject of the research were 21. Among them, 7 were managers, 6 professional and 8 family/caregivers. For the interpretation of empirical material we use thematic analysis. Resolution N° 196/96 National Health Council, and resolution COFEN no 311/2007 guided the development of this research. In the process of analysis of the empirical material resulted in three categories: Hospitalization and Schooling: implications of remoteness and coping strategies; Formal Schooling in Hospital: knowledge of the laws imposed; Pedagogical care Hospital: perception of managers and professionals. These categories have revealed hospitalization is shown that considered moment that makes the child/teenage experience painful experiences due to the remoteness of friends and daily routine; the idleness and lack of activities that will remember the school everyday cause child/teenage retract themselves and forget the healthy childhood. Family members and professionals they blame the management for the non fulfillment of hospital school service polictic, in the absence of that family care seeks ways of tackling school losses of their children. Sometimes managers do not believe that the family recognizes the importance of education for the life of their children. The limited perception of possibility of continuity of cognitive and intellectual formation process demonstrates lack of knowledge and sensitivity of some managers and professionals. Therefore, we infer that, the lack of hospital grade is fact, so we call attention to the need for a face-to-face discussion that should result in effectiveness/implementation this educational strategy. The problems faced by children and adolescents have urgency to be solved, and should be addressed, thus avoiding the aggravation of the situation and the losses. We believe that the political will and looks more human and less welfare of managers will be able to consolidate the implementation of public policies imposed.